2021
DOI: 10.21776/ub.jepa.2021.005.03.12
|View full text |Cite
|
Sign up to set email alerts
|

Motivasi Petani dalam Usahatani Pembibitan Padi (Studi Kasus di Desa Ngumpakdalem Kecamatan Dander Kabupaten Bojonegoro)

Abstract: Rice is the staple food of Indonesian society which cannot be replaced by other staples. The earliner stage in rice cultivation is nursery or seedbed stage. Ngumpakdalem village has a field area of 602,74 hectares, but there are only 30 farmers who work in rice nurseries, because farmers think that rice nursery businesses must be have an expertise, time enough, need a lot of capital, and has some risks. The purpose of this study are to determine the characteristics of farmers who cultivate rice nurseries in Ng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
2
0
4
Order By: Relevance
“…and it can be concluded that the length of farming business has a negative effect on the Motivation of Smallholders in performing castration. Also reinforced by research by Asfiati & Sugiarti (2021), there is a significant negative effect on the level of motivation of smallholders in rice breeding farming. This is because the majority of smallholders 5-10 years of farming experience (still relatively low), with this experience smallholders are more motivated to develop their rice nursery farms.…”
Section: Farming Experiencementioning
confidence: 98%
“…and it can be concluded that the length of farming business has a negative effect on the Motivation of Smallholders in performing castration. Also reinforced by research by Asfiati & Sugiarti (2021), there is a significant negative effect on the level of motivation of smallholders in rice breeding farming. This is because the majority of smallholders 5-10 years of farming experience (still relatively low), with this experience smallholders are more motivated to develop their rice nursery farms.…”
Section: Farming Experiencementioning
confidence: 98%
“…Berdasarkan hal tersebut, terdapat kesamaan dengan penelitian Herminingsih (2014) mengemukakan bahwa umur sama sekali tidak berpengaruh terhadap perilaku seseorang, karena pengalaman dan keadaan di lapangan lebih mempengaruhi petani dalam melakukan usahatani. Hal ini juga sependapat dengan Astuti (2014), bahwa tidak ada hubungan nyata antara umur dengan perilaku petani, karena semua golongan umur, tua ataupun muda,samasama memiliki kesempatan yang sama dalam mengerjakan sesuatu.…”
Section: Umur (X1)unclassified
“…Penentuan lahan perkebunan merupakan langkah awal yang dilakukan petani dalam melakukan budidaya jagung. Pada tahap ini, petani melakukan musyawarah (dopoghwa-ghawa) terlebih dahulu guna membahas tentang luas lahan, batas-batas lahan serta jika terdapat petani yang tidak memilki lahan, maka petani lainnya akan meminjamkan lahannya dengan catatan petani yang bersangkutan mau berkebun dalam rangka memenuhi kebutuhan hidupnya.. Menurut Astuti (2014), intensitas pertemuan yang diselenggarakan petani merupakan salah satu upaya untuk meningkatkan motivasi petani dalam kegiatan pertanian, dalam hal ini adalah kegiatan usahatani jagung. Oleh karena itu, dalam tahap penentuan lahan, maka sangat diperlukan bermusyawarah terlebih dahulu guna membahas tentang persiapan lahan yang akan diolah.…”
Section: Penentuan Lahan Perkebunan (Deghondo Tampa)unclassified